Properties of nano-silica modified pervious concrete - Mohammed, B.S. (Elsevier Ltd, 2018)
The aim of this study is to evaluate the effects of inclusion nano-silica (also known as nano-SiO2) on the properties of pervious concrete containing fly ash (FA) as a partial replacement to cement. It has been found, for cementitious paste, that incorporating NS leads to reduce the cumulative pore volume by 13.4. While the compressive strength of NS modified pervious concrete has been improved without adversely affecting its void ratio and permeability. The workability has been adversely affected by the inclusion of NS, which can be enhanced by incorporating the fly ash and superplasticizer. The porosity of cementitious paste has increased as the FA content is increased. These results are in good agreement with SEM results. For the pervious concrete voids ratio, permeability and infiltration rate were decreased against the increase of paste to the aggregate ratio Response surface methodology (RSM) has also been used to develop a model for navigating the design space of NS modified pervious concrete. Models revealed 95 significance of confidence level with difference less than 0.2 between Pred R-Squared value of 0.9515 and Adj R-Squared. The general expression has been developed for all the responses with the different coefficients using the RSM. Â© 2018